2015
DOI: 10.1007/s00128-015-1511-y
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides for Apicultural and/or Agricultural Application Found in Belgian Honey Bee Wax Combs

Abstract: In a Belgian pilot study honey bee wax combs from ten hives were analyzed on the presence of almost 300 organochlorine and organophosphorous compounds by LC–MS/MS and GC–MS/MS. Traces of 18 pesticides were found and not a single sample was free of residues. The number of residues found per sample ranged from 3 to 13, and the pesticides found could be categorized as (1) pesticides for solely apicultural (veterinary) application, (2) pesticides for solely agricultural (crop protection) application, (3) pesticide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 21 publications
1
57
0
Order By: Relevance
“…Furthermore, in West Africa, honey bees mainly collect nectar during the dry season when the usage of pesticides is limited. Finally pesticides show more affinity to beeswax compared to honey (Ravoet et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in West Africa, honey bees mainly collect nectar during the dry season when the usage of pesticides is limited. Finally pesticides show more affinity to beeswax compared to honey (Ravoet et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Miticides originating from beekeeping practices, as well as veterinary drugs (e.g., farm uses), can also contribute to the composition of the xenobiotic complex. Such level of exposure has been confirmed by numerous studies using residue analysis of bees and hive matrices (for examples, see Bogdanov 2006;Chauzat et al 2009;Mullin et al 2010;Lambert et al 2013;Ravoet et al 2015).…”
Section: Introductionmentioning
confidence: 66%
“…Contaminants from the environment can reach the raw materials of bee products and can be transported to the hive as a consequence of bees' physiological activities (34)(35). It is also known that pesticides and acaricides used in regular beekeeping practices, or other fat soluble and persistent substances, can easily accumulate within (24). Recently, Reddy et al (36) concluded that honeycomb biomass is an environmentally friendly and attractive option for removing heavy metal ions from water or wastewater.…”
Section: Resultsmentioning
confidence: 99%
“…There are very few studies on the heavy metal contamination of beeswax (24), and data on its influence on comb foundation quality, as well as the correlations with the rearing and biological characteristics of honeybee brood in contaminated combs are insufficient. It is not known how effective the production of casting comb foundations with a long sedimentation and cooling period is in reducing heavy metal concentrations.…”
mentioning
confidence: 99%